2022
DOI: 10.1038/s41598-022-18547-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastic incorporation into an organismal skeleton

Abstract: Studies on the effects of global marine plastic pollution have largely focused on physiological responses of few organism groups (e.g., corals, fishes). Here, we report the first observation of polymer nanoparticles being incorporated into the calcite skeleton of a large benthic foraminifera (LBF), a significant contributor to global carbonate production. While previous work on LBF has documented selectivity in feeding behaviour and a high degree of specialization regarding skeletal formation, in this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…1). Protists were critically underrepresented (i.e., 2%) and amongst the 24 papers that considered them, ten of these studies focused on benthic foraminifera; amongst which four observed benthic 7 foraminifera on floating and benthic plastic debris (Jorissen 2014, Finger 2017, Birarda et al 2021, ub as-Baratau et al 2022, four focused on the inclusion of plastic particles in foraminiferal tests (Tsuchiya and Nomaki 2019, Birarda et al 2021, Joppien et al 2022a, Romano et al 2023) and only four stricto sensu monitored the effect of MPs or NPs (Ciacci et al 2019, Birarda et al 2021, Joppien et al 2022b. A recent review (Delaeter et al 2022) showed that, in plastic leachates-related studies, only 0.64% studies considered benthic foraminifera, while about 98% were on macro-invertebrates.…”
Section: Plastic Pollution and Benthic Foraminifera: The Big Voidmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Protists were critically underrepresented (i.e., 2%) and amongst the 24 papers that considered them, ten of these studies focused on benthic foraminifera; amongst which four observed benthic 7 foraminifera on floating and benthic plastic debris (Jorissen 2014, Finger 2017, Birarda et al 2021, ub as-Baratau et al 2022, four focused on the inclusion of plastic particles in foraminiferal tests (Tsuchiya and Nomaki 2019, Birarda et al 2021, Joppien et al 2022a, Romano et al 2023) and only four stricto sensu monitored the effect of MPs or NPs (Ciacci et al 2019, Birarda et al 2021, Joppien et al 2022b. A recent review (Delaeter et al 2022) showed that, in plastic leachates-related studies, only 0.64% studies considered benthic foraminifera, while about 98% were on macro-invertebrates.…”
Section: Plastic Pollution and Benthic Foraminifera: The Big Voidmentioning
confidence: 99%
“…Foraminifera have mainly four types of tests: those that assemble calcium carbonate crystals constructed intracellularly and build tests (porcelaneous test), those that crystallized calcium carbonate (mainly) extracellularly (hyaline), those that collect sediment particle in the habitat for a test (agglutinated), and those with an organic membrane. Plastic particles were found to be included in the test of hyaline (Joppien et al 2022a) and agglutinated foraminifera (Tsuchiya and Nomaki 2019, Birarda et al 2021, Romano et al 2023, and, as such, might further be transferred to predators of foraminifera like gastropods, copepods, polychaetes, decapods, polychaetes and fishes (Buzas and Carle 1979, Culver and Lipps 2003, Nomaki et al 2008. Inclusion of plastic particles into the test of benthic foraminifera may likely expose them to the harmful effects of plastic additives; see Delaeter et al (2022) for a specific review on the impacts of plastic leachates on organisms.…”
Section: Plastic Pollution and Benthic Foraminifera: The Big Voidmentioning
confidence: 99%
See 1 more Smart Citation